Entrepreneurship Influenced by Education and Ethnicity - Klisarovska, Elena (Mediterranean Journal of Social Sciences, 2012)
Although entrepreneurship as a process has been present for centuries, entrepreneurship as an academic area of study hasbeen introduced recently. And, like other economic and social disciplines it does not have clear-cut borders. Instead it overlaps, drawsupon, complements and includes other areas of study including business and management, sociology, psychology, economics, finance,and public policy. This is a multidisciplinary research study among Albanian and Macedonian students in Macedonia with the aim tostudy the development of entrepreneurship in Macedonia, to observe factors that are triggering and fueling entrepreneurial mindsets andwhat makes people want to become entrepreneurs with socio-demographic characteristics, especially ethnicity and cultural differences,of the students interviewed under review (gender, age, level of education completed, occupation, parents’ occupation and locality –urbanor rural)